Assessment of Productivity and Compatibility of Komatsu PC 2000 Loader and Komatsu HD 785 Transport Equiptment in Overburden Stripping Activities in the North Pit of Muara Tiga Besar Mining Area at PT. Bukit Asam, Tbk. Tanjung Enim, South Sumatra - Putra Alfarizi; Heri Prabowo (Departemen Teknik Pertambangan FT UNP, 2024)
PT. Bukit Asam, Tbk is a coal mining company with an IUP area of 14,987 Ha (PT Bukit Asam, Tbk, 2018), the mining location is located in Tanjung enim, Lawang Kidul sub-district, Muara Enim Regency, South Sumatra Province which is divided into 3 Mining Business License Areas namely: Air Laya Mine (TAL), West Bangko Mine and Muara Tiga Besar Mine. Coal mining in Muara Tiga Besar Mining area of PT Bukit Asam company. Using Komatsu PC 400 for coal getting activities, while for overburden uses Komatsu PC 2000, PC 1250 and PC 800. For transportation equipment in the form of Dump Truck HINO 500 FM 320 TI for coal getting activities and HD 785 for overburden. The productivity value of the PC2000 digging tool for overburden is 750.02 bcm / hour, while for HD for overburden is 96.866 bcm / hour. For the MF (match factor) value on the PC 2000 with HD 785 for overburden is 0.89, meaning that there is a mismatch between the PC 2000 and HD 785 because the MF value < 1 so that there is waiting time for the PC 2000 digging tool for the HD 785 conveyance.